Islamic law as administered in Sarawak: a survey / Arni Noor - Noor, Arni (Faculty of Law, 1982)
The law pertaining to the administration of muslim law has recently undergone a change with the introduction of the Syariah Court to replace the Native Courts in administrating muslim law. This change is brought about by the Majlis Islam (Incorp) (Amend) Ordinance 1978. The object of this paper is therefore to see the extent of the scope of the Syariah Courts in Sarawak. This would be interesting as now muslim law and Malay customs will no longer be decided in the Native Courts. Hope is there that the muslim law be better administered through the amended Ordinance 1978 rather than through the controversial decisions made by the Native Courts. In order therefore to analyse the extent and ambit of this Syariah Court, it is necessary to discuss the development of muslin law since James Brooke took over this state in 1841. This is to enable one to appreciate the existing decisions as made by the Native Courts. The scope of this paper therefore does not limit itself merely to the present day. In going about with my project, I had conducted interviews with the staff of the District Native Court, Kuching and where I had a study of the cases decided in 1981 Pertaining to Malay customs and muslim law. Interviews are also conducted with the Majlis Islam Sarawak as to the prospect of muslim law in Sarawak in the light of the new